Primary Malignant Melanoma in the Pineal Region: Case Report and Literature Review - Wendel, Christopher; Kaech, Denis Laurent; Woodtli, Martin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Primary pineal malignant melanoma is a rare type of primary central nervous system melanoma with only 19 cases reported in the literature.Case Report We present a case of a 53-year-old man with primary melanoma of the pineal region. He presented to the emergency department with gait unsteadiness and ataxia. Magnetic resonance imaging (MRI) revealed a 22 × 17 × 22-mm mass in the pineal region. On MRI the tumor was hyperintense in T1, isointense in T2, and on T1-weighted images with gadolinium enhancement it appeared homogeneously hyperintense with hypointense spots. Our patient underwent subtotal tumor resection as well as radiotherapy. The 52-week MRI control showed no recurrence of the lesion.After 62 weeks he developed gait ataxia and headaches and was admitted to the emergency department. Computed tomography revealed tumor bleeding and obstructive hydrocephalus.An external ventricular drain was placed, but the bleeding progressed, and 7 days after admission, MRI showed bleeding in the thalamus and mesencephalon. With a dismal prognosis, therapy was discontinued. He died 65 weeks after diagnosis.Methods We reviewed the available literature (PubMed) with 19 published cases of primary pineal malignant melanoma and evaluated the common symptoms at presentation, histopathologic features, radiologic findings, therapeutic regimens, and time of survival to provide the most up-to-date treatment.Results The median age of patients with primary pineal malignant melanoma is 52 years (female-to-male ratio: 10:10 years); a common first sign is chronic hydrocephalus. On MRI the lesion presents hyperintense in T1 and hypo- to isointense in T2. Biopsy or resection and histopathologic analysis are the key to diagnosis. Common histopathologic features are melanic pigment (n = 19/20), positive Human Melanoma Black (HMB-45) marker (n = 13/20), positive S100 protein reactivity (n = 11/20), as well as positive Melan-A (n = 9/20). The median survival was > 56.5 weeks in patients treated with resection and radiation.Conclusion Reconsidering the reported cases surgical treatment followed by radiation increases the length of survival.
Keywords: primary; pineal; malignant; melanoma; central nervous system